2003
DOI: 10.1034/j.1600-0889.2003.00041.x
|View full text |Cite
|
Sign up to set email alerts
|

Cloud condensation nuclei spectra derived from size distributions and hygroscopic properties of the aerosol in coastal south-west Portugal during ACE-2

Abstract: In this work we propose and test a method to calculate cloud condensation nuclei (CCN) spectra based on aerosol number size distributions and hygroscopic growth factors. Sensitivity studies show that this method can be used in a wide variety of conditions except when the aerosol consist mainly of organic compounds. One crucial step in the calculations, estimating soluble ions in an aerosol particle based on hygroscopic growth factors, is tested in an internal hygroscopic consistency study. The results show tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 54 publications
1
57
0
Order By: Relevance
“…into the CCN prediction algorithm [Covert et al, 1998;Dusek et al, 2003;Ervens et al, 2007;Snider et al, 2003;Zhou et al, 2002]. Some studies assumed internally mixed aerosols but treated clearly bimodal scans separately [Rissler et al, 2004;Vestin et al, 2007], or involved the full GF-PDF [Gasparini et al, 2006;Mochida et al, 2006] similar to our study.…”
Section: Comparison To Previous Studiesmentioning
confidence: 97%
See 1 more Smart Citation
“…into the CCN prediction algorithm [Covert et al, 1998;Dusek et al, 2003;Ervens et al, 2007;Snider et al, 2003;Zhou et al, 2002]. Some studies assumed internally mixed aerosols but treated clearly bimodal scans separately [Rissler et al, 2004;Vestin et al, 2007], or involved the full GF-PDF [Gasparini et al, 2006;Mochida et al, 2006] similar to our study.…”
Section: Comparison To Previous Studiesmentioning
confidence: 97%
“…Most studies assumed internally mixed aerosols, involving only GF mean (D p ,t) instead of the full GF-PDF Figure 7. Closure performances as a function of SS of different CCN activation closure studies for atmospheric aerosols that used HTDMA data as a proxy for the chemical composition [Covert et al, 1998;Dusek et al, 2003;Ervens et al, 2007;Gasparini et al, 2006;Mochida et al, 2006;Rissler et al, 2004;Snider et al, 2003;Vestin et al, 2007;Zhou et al, 2002]. Results obtained in this study (externally mixed approach) are shown as black circles.…”
Section: Comparison To Previous Studiesmentioning
confidence: 99%
“…Critical super-saturations given in Hudson and Da (1996) for measurements in Reno, Nevada, are 0.3% and 0.23% for particle sizes of 60 and 100 nm, and for measurements done in Sacramento, California, are 0.5% and 0.45% for 60 and 100 nm, respectively. Recently, Dusek et al (2006) obtained a critical diameter of 83 nm at a super-saturation of 0.4% for an air mass that recently had passed over the city of Frankfurt, Germany. Thus, the values measured in this study are in the same range than earlier measurements of the CCN behavior of urban atmospheric aerosol particles.…”
Section: Activationmentioning
confidence: 99%
“…In the past, attempts have been made to derive the number of cloud condensation nuclei (CCN) of an aerosol from measurements of hygroscopic properties (e.g., Covert et al, 1998;Dusek et al, 2003). Generally, the derived number of CCN overestimates the number of CCN measured.…”
Section: Hygroscopic Growthmentioning
confidence: 99%
See 1 more Smart Citation